A high-efficiency grating coupler between single-mode fiber and silicon-on-insulator waveguide *Project supported by the National Key Research and Development Program of China (No. 2016YFB0402404), the High-Tech Research and Development Program of China (Nos. 2013AA031401, 2015AA016902, 2015AA016904), and the National Natural Foundation of China (Nos. 61674136, 61435002, 61176053, 61274069). (June 2017) - Liu, Rongrui; Wang, Yubing; Yin, Dongdong; Ye, Han; Yang, Xiaohong; Han, Qin
Abstract: We present the design of a diffractive grating structure and get the optimal parameters which can achieve more than 75% coupling efficiency (CE) between single-mode fiber and silicon-on-insulator (SOI) waveguide through 2D finite-different time-domain (FDTD) simulation. The proposed architecture has a uniform structure with no bottom reflection element or silicon overlay. The structure, including grating couplers, adiabatic tapers and interconnection waveguides can be fabricated on the SOI waveguide with only a single electron-beam lithography (ICP) step, which is CMOS-compatible. A relatively high coupling efficiency of 47.2% was obtained at a wavelength of 1562 nm.